UJI PARAMETER FISIKA, KIMIA DAN BIOLOGI PADA BUDIDAYA LOBSTER AIR LAUT DI PANTAI EKAS KABUPATEN LOMBOK TIMUR - Dwi Cahya Abadi Putra; Muhammad Junaidi; Dewi Putri Lestari (Jurnal Media Akuakultur Indonesia, 2022)
Lobster is one of the marine biota that has high economic value, as well as being one of the biota that can be developed through the cultivation process. The waters of Ekas Bay have the potential of marine resources that can be used as a place for lobster cultivation. This study aims to determine water quality with physical, chemical and biological parameters for lobster cultivation on the former coast of East Lombok Regency. The research was carried out in April 2022, located in the waters of Ekas Bay and the Lombok Marine Aquaculture Fisheries Laboratory Laboratory, West Sekotong, West Lombok Regency. Observations of the research were carried out in situ to observe water quality, as well as taking samples using a random sampling method of 8 points and then observing the content of nitrate, nitrite and plankton in the laboratory. The data that has been obtained is then analyzed descriptively by comparing the data with quality standards and ideal conditions for the development of sea crayfish aquaculture. The results showed that the water quality in Ekas Bay was generally in an ideal condition to be used as a lobster culture based on the appropriate quality standards of water quality for lobster cultivation. The water areas that are very suitable to be used as a place for lobster cultivation based on quality standards of water quality are the KJA 1, KJA 2, KJA 3 and Seagrass areas. The plankton species found consisted of Amphisolenia sp., Coscinadiscus sp., Nitzchia sp., Moina sp., Planktoniella sp., Oithona sp., Synedra sp. and Navicula sp.